2021
DOI: 10.4085/1062-6050-0021.21
|View full text |Cite
|
Sign up to set email alerts
|

High School Sport Specialization and Injury in Collegiate Club-Sport Athletes

Abstract: Context: Sport specialization during adolescence may affect future injury risk. This association has been demonstrated in some professional sports athletes. Objective: Determine the association between adolescent sport specialization levels in high school and injuries sustained during collegiate club sports. Design: Cross-sectional study. Setting: Paper and online surveys. Patients: Collegiate club sport athletes. Intervention: An anony… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 27 publications
0
10
0
1
Order By: Relevance
“…In contrast, expertise from extracurricular sports participation might influence injury risks for specific intracurricular sports. 36 These and other possible factors contributing to intracurricular injury risks need to be investigated from a socioecological perspective to develop adequate preventive and rehabilitative measures. 10 A limitation of our analyses based on incidence rates is that the burden of injuries, apart from incidence rate, exposure time and the number of participants, is affected by the injury duration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, expertise from extracurricular sports participation might influence injury risks for specific intracurricular sports. 36 These and other possible factors contributing to intracurricular injury risks need to be investigated from a socioecological perspective to develop adequate preventive and rehabilitative measures. 10 A limitation of our analyses based on incidence rates is that the burden of injuries, apart from incidence rate, exposure time and the number of participants, is affected by the injury duration.…”
Section: Discussionmentioning
confidence: 99%
“…High increases in cumulative intracurricular and extracurricular exposure times might contribute to higher injury risks during the first year. In contrast, expertise from extracurricular sports participation might influence injury risks for specific intracurricular sports 36. These and other possible factors contributing to intracurricular injury risks need to be investigated from a socioecological perspective to develop adequate preventive and rehabilitative measures 10…”
Section: Discussionmentioning
confidence: 99%
“…In our study, single-sport specialization was common, but 47% of pitchers still played other sports. Biese et al (2021) 2 conducted a survey study and found that 79% of collegiate athletes were multisport athletes in high school. Rugg et al (2020) 22 conducted a similar survey study of collegiate athletes and found that baseball athletes were more likely to specialize later in their careers than gymnasts, tennis players, swimmers, and soccer players.…”
Section: Discussionmentioning
confidence: 99%
“… 10 , 18 , 19 , 20 Two prior survey studies at the collegiate level were unable to find any association between injury and a history of single-sport specialization. 2 , 22 However, a study of professional baseball players did demonstrate a relationship between early single-sport specialization and injury while playing professionally. 25 Two prior studies at the high school level have demonstrated an association between single-sport specialization and risk for injury in high school athletes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation